2009
DOI: 10.1155/2009/892569
|View full text |Cite
|
Sign up to set email alerts
|

Fourier transform infrared spectroscopy of dental unit water line biofilm bacteria

Abstract: Abstract. Fourier transform-infrared (FT-IR) spectroscopy has become an important tool for rapid analysis of complex biological samples. The infrared absorbance spectrum could be regarded as a "fingerprint" which is a feature of biochemical substances. The FT-IR spectra of fresh and stored dried samples of six bacterial isolates (Klebsiella sp., Bacillus cereus, Bacillus subtilis, Pseudomonas aeruginosa, Achromobacter xylosoxidans and Achromobacter sp.) were observed by variation in sample preparation. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…FTIR of P. aeruginosa AgNPs was performed to check the involvement of biological molecules. The bands present at 3261, 3061, 2947, 2358, 1338 and 1394 cm −1 corresponded to the stretching vibrations of alcohol (O-H) , primary amines (N-H) , alkane (C-H) , amine (C-N) and alcohol (C-O) groups respectively, as reported previously by Liaqat 35) and Kalyanasundaram et al 36) . The SEM data showed that silver nanoparticles are in spherical shape with average size of 40 nm.…”
Section: Discussionsupporting
confidence: 79%
“…FTIR of P. aeruginosa AgNPs was performed to check the involvement of biological molecules. The bands present at 3261, 3061, 2947, 2358, 1338 and 1394 cm −1 corresponded to the stretching vibrations of alcohol (O-H) , primary amines (N-H) , alkane (C-H) , amine (C-N) and alcohol (C-O) groups respectively, as reported previously by Liaqat 35) and Kalyanasundaram et al 36) . The SEM data showed that silver nanoparticles are in spherical shape with average size of 40 nm.…”
Section: Discussionsupporting
confidence: 79%
“…The bands at 3,695, 1,622, 1,520, 1,124, 1,032, 914, 600, and 475 cm −1 can be used to distinguish hematite from biological structures. A small organic component is indicated by the bands for the -CH 3 and -CH groups (2,960, 2,869, 2,930, and 2,849 cm −1 ), which are evident in our FTIR analysis results of the fatty-acid region (Bosch et al, 2006;Liaqat, 2009). As Figure 4 shows the attached biofilm on the electrodes are irreversible.…”
Section: Ftir Spectra Analysis Of Biofilmsmentioning
confidence: 52%
“…Additionally, variations in the fatty acid-region peak could indicate a biological change. Proteins (amide I, II, and III bands), nucleic acids (regions around 1,240 and 1,080 cm −1 ), polysaccharides (from 1,150 to 900 cm −1 ), and lipids (around 2,900 cm −1 ) are the main groups of biomolecules (Bosch et al, 2006; Liaqat, 2009;You et al, 2015) that can be associated with the observed bands. The strong band at 1,646 cm −1 observed in the biofilms may partially be the result of the H-O-H bending (ν2 mode) band of water.…”
Section: Ftir Spectra Analysis Of Biofilmsmentioning
confidence: 99%
“…A band of IR spectra from 1850 to 1350 cm −1 includes a band in the region of 1730 cm −1 that can be attributed to (>C=O) phospholipids, esters, fatty acids [ 28 , 29 , 43 , 48 ], and the characteristic region of proteins. Protein bands include Amide I (C=O stretch) vibrations in the region from 1675–1615 cm −1 , Amide II (60% N–H bend and 40% C–N stretch) vibrations in the region from 1575–1520 cm −1 , and Amide III (40% C–N stretch, 30% N–H bend) vibrations in the region from 1315–1270 cm −1 [ 28 , 29 , 41 , 42 , 43 , 45 ].…”
Section: Resultsmentioning
confidence: 99%